The apple lover's cookbook - Traverso, Amy (W. W. Norton & Company, 2020)
"The Apple Lover's Cookbook is more than a recipe book. It's a celebration of apples in all their incredible diversity, as well as an illustrated guide to 70 popular (and rare-but-worth-the-search) apple varieties. Each has its own complete biography with entries for best use, origin, availability, season, appearance, taste, and texture. Amy Traverso organizes these 70 varieties into four categories--firm-tart, tender-tart, firm-sweet, and tender-sweet--and includes a one-page cheat sheet that you can refer to when making any of her recipes. More than 100 scrumptious, easy-to-make recipes follow, offering the full range from breakfast dishes, appetizers, salads, soups, and entrees all the way to desserts. On the savory side, there's a cider-braised brisket and a recipe for Sweet Potato-Apple Latkes. On the sweet side, Amy serves up crisps, cobblers, pies, and cakes, including Apple-Pear Cobbler, Cider Donut Muffins, and an Apple-Cranberry Slab Pie cut into squares to eat by hand. As bonuses, The Apple Lover's Cookbook contains detailed notes on how to tell if an apple is fresh and guides to apple festivals, ciders, and products, as well as updated information about the best times and places to buy apples across the United States, making it easy to seek out and visit local orchards, whether you live in Vermont or California. First published a decade ago, now newly revised and updated, The Apple Lover's Cookbook is your lifetime go-to book for apples"--